Effects of Histidine-rich glycoprotein on erythrocyte aggregation and hemolysis: Implications for a role under septic conditions - Hui Zhong; Hidenori Wake; Keyue Liu; Yuan Gao; Kiyoshi Teshigawara; Masakiyo Sakaguchi; Shuji Mori; Masahiro Nishibori (Elsevier, 2018)
The apoptotic process of erythrocytes is known as eryptosis, and is characterized by phosphatidylserine (PS) expression on the outer membrane. PS-positive erythrocytes are increased in sepsis, and PS is believed to facilitate coagulation of erythrocytes and activate macrophages. However, the relationship between eryptosis and abnormal coagulation in sepsis is still not fully understood.Histidine-rich glycoprotein (HRG) inhibits immunothrombus formation by regulating neutrophils and vascular endothelial cells. In the present study, we subjected isolated erythrocytes to Zn2+ stimulation, which activated their aggregation and PS expression. We then determined the Zn2+ contents in septic lung and kidney tissues, and found that they were elevated, suggesting that eryptosis was enhanced in these tissues. Erythrocyte adhesion to endothelial cells was also significantly increased after Zn2+ stimulation, and this effect was inhibited by HRG. Finally, we examined HRG treatment in septic model mice, and found that HRG decreased hemolysis, possibly due to its ability to bind heme.Our study demonstrated a novel Zn2+-initiated aggregation/thrombus formation pathway. We also showed the regulatory role of HRG in this pathway, together with the ability of HRG to inhibit hemolysis under septic conditions. HRG supplementation might be a novel therapeutic strategy for inflammatory disorders, especially sepsis. Keywords: Eryptosis, Aggregation, Hemolysis, Sepsis, Histidine-rich glycoprotein (HRG)